Efficacy of photobiomodulation in the treatment of avulsed teeth: A systematic review of animal studies - Figueiredo, Leonardo Raniel [UNESP]; Bento, Victor Augusto Alves [UNESP]; Sonoda, Celso Koogi [UNESP]; Pellizzer, Eduardo Piza [UNESP] (Springer Nature, 2024)
The objective of this systematic review was to evaluate the effectiveness of photobiomodulation therapy (PBM) in managing avulsed teeth. This systematic review was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-analyses (i.e., “PRISMA”) statement 2020 and was registered in the International Prospective Register of Systematic Reviews (i.e., PROSPERO) with number CRD42022362198. The participants, intervention, comparison, outcomes, and study design (i.e., PICOS) for the present study considered the following question: “Does the use of laser PBM in the treatment of teeth with avulsion influence tissue repair performance?” A literature search was performed in PubMed/MEDLINE, Embase, Web of Science, Cochrane Library, and ProQuest databases until January 2023. The SYRCLE’s RoB tool (Systematic Review Center for Laboratory Animal Experimentation) for animal studies were used for quality assessment. A total of 7 in vivo studies published between 2011 and 2018 were included in this systematic review for qualitative analysis. All studies used Wistar rats, totaling 368 specimens that simulated tooth avulsion trauma. The effect of photodynamic therapy in the treatment of avulsed teeth was positive in 5 studies (significant increase in tissue repair) and negative in 2 studies, in which both studies with negative results kept teeth in saline solution before reimplantation and showed the longest time and power of laser application. PBM appears to be effective for tissue repair in the treatment of avulsed teeth, depending on the means of conservation of the avulsed tooth and the laser application protocol.
Keywords: Avulsed teeth; Laser photobiomodulation; Repair performance; Systematic review